Combined hearing and vision screening programs: A scoping review - Oosthuizen, Ilze; Frisby, Caitlin; Chadha, Shelly; Manchaiah, Vinaya; Swanepoel, De Wet (Frontiers in Public Health, 2023)
Background and aim The World Health Organization (WHO) estimates that 1.5 billion and 2.2 billion people have hearing and vision impairment, respectively. The burden of these non-communicable diseases is highest in low- and middle-income countries due to a lack of services and health professionals. The WHO has recommended universal health coverage and integrated service delivery to improve ear and eye care services. This scoping review describes the evidence for combined hearing and vision screening programs. Method A keyword search of three electronic databases, namely Scopus, MEDLINE (PubMed), and Web of Science, was conducted, resulting in 219 results. After removing duplicates and screening based on eligibility criteria, data were extracted from 19 included studies. The Joanna Briggs Institute Reviewer Manual and the Preferred Reporting Items for Systematic Reviews and Meta-analyzes (PRISMA) Extension for Scoping Reviews were followed. A narrative synthesis was conducted. Results Most studies (63.2%) were from high-income countries, with 31.6% from middle-income and 5.2% from low-income countries. The majority of studies (78.9%) involved children and the four studies reporting on adults all included adults above 50 years of age. Vision screening was most commonly performed with the “Tumbling E” and “Snellen Chart,” while hearing was typically screened using pure tone audiometry. Studies reported referral rates as the most common outcome with sensitivity and specificity rates not reported in any included articles. Reported benefits of combined vision and hearing screenings included earlier detection of vision and hearing difficulties to support functioning and quality of life as well as resource sharing for reduced costs. Challenges to combined screening included ineffective follow-up systems, management of test equipment, and monitoring of screening personnel. Conclusions There is limited research evidence for combined hearing and vision screening programs. Although potential benefits are demonstrated, especially for mHealth-supported programs in communities, more feasibility and implementation research are required, particularly in low- and middle-income countries and across all age groups. Developing universal, standardized reporting guidelines for combined sensory screening programs is recommended to enhance the standardization and effectiveness of combined sensory screening programs.